The Effect of Human Resource Management Strategies on the Market Competitiveness of Multinational Companies - Zhou, Yihan (Transactions on Economics, Business and Management Research, 2024)
In today's context of global economic integration, multinational corporations (MNCs) are facing unprecedented market challenges and opportunities. This paper deeply explores how human resource management, as a core driving force, influences and enhances the market competitiveness of multinational corporations (MNCs). Through an extensive review of domestic and international related literature and case studies of successful MNCs, this paper systematically investigates the multidimensional mechanisms of efficient HRM practices. The results show that these practices not only significantly enhance the market adaptability of MNCs, enabling them to respond quickly to environmental changes. They also effectively stimulate the innovation vitality within the organization and promote the continuous iteration and upgrade of products and services, and at the same time, they also significantly improve the brand influence of the enterprise and enhance market recognition. Based on this, this paper provides multinational corporations with specific suggestions for optimizing human resource management strategies, aiming to help them build stronger market competitiveness, and this research result is of great practical significance to the strategic planning and daily management of multinational corporations.